2023
DOI: 10.3389/fevo.2023.1139053
|View full text |Cite
|
Sign up to set email alerts
|

Both species richness and growth forms affect nutrient removal in constructed wetlands: A mesocosm experiment

Abstract: IntroductionPlant richness is thought to improve the function of constructed wetlands (CWs), but most CWs are planted with monocultures, with only a few employed polycultures, which have drawn contradictory conclusions. We suppose functional diversity is the key to better performance of plant communities and hypothesize that CWs planted with diverse growth forms are superior in plant growth and nutrient removal.MethodsIn this study, six emergent plant species categorized into slender type (Schoenoplectus taber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…LECs that are comprised of multiple species demonstrated higher levels of multifunctionality at low-medium levels compared to monocultures, due to the advantage of including species that are effective in several ecosystem functions (Riis et al, 2018) and complementarity in timing of growth that ensures functions are better delivered (Luo et al, 2023;Manolaki et al, 2020). However, as the performance threshold became higher (75 %), the monoculture plant community (e.g., Typha latifolia) was most effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LECs that are comprised of multiple species demonstrated higher levels of multifunctionality at low-medium levels compared to monocultures, due to the advantage of including species that are effective in several ecosystem functions (Riis et al, 2018) and complementarity in timing of growth that ensures functions are better delivered (Luo et al, 2023;Manolaki et al, 2020). However, as the performance threshold became higher (75 %), the monoculture plant community (e.g., Typha latifolia) was most effective.…”
Section: Discussionmentioning
confidence: 99%
“…Assembling plants in mixed stature communities appears to negatively influence above-ground tissue concentrations of nutrients/major ions, likely due to antagonistic interactions between large emergent species and smaller species (Luo et al, 2023). Additionally, the water in the mesocosm containing the MECs had comparatively higher levels of dissolved oxygen suggesting lower productivity and root turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the effluent, they were 4-10 mg/L and 0-3 mg/L, respectively (Figure 2), except for ammonia (average 80.8 ± 8.7 mg/L) and phosphate (average 86.7 ± 10.6 mg/L), the pollutant measured did not show statistically (p > 0.05) different removal rate between polycultures and monocultures with Canna hybrids (75-80%; p > 0.05), compared with the removal in monoculture CWs of Dieffenbachia seguine (63-68%; p < 0.05). Luo et al [35] indicated that plant communities with various growth forms reduced the intensity of interspecific competition, increased functional diversity, and greatly enhanced the ability to consume nitrogen and phosphorous compounds.…”
Section: Pollutant Concentrations and Removalsmentioning
confidence: 99%
“…This promotes the evolution of entities or systems through a certain dynamic regulatory mechanism to achieve coordinated and synchronized development. Current research on synergistic development focuses on various areas, including regional economic or city cluster synergistic development [13][14][15][16], industrial synergistic development [17][18][19][20], and synergistic development of economic-environmental composite systems [21][22][23], among others.…”
Section: Research On Synergistic Developmentmentioning
confidence: 99%